1986
DOI: 10.1182/blood.v67.6.1765.1765
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of morphology and karyotype in primary myelodysplastic syndromes

Abstract: Forty-nine patients with primary myelodysplastic syndromes (MDS) were subclassified according to French-American-British (FAB) Cooperative Group criteria. Eight patients had acquired idiopathic sideroblastic anemia (AISA), ten had chronic myelomonocytic leukemia (CMMoL), 14 had refractory anemia (RA), nine had refractory anemia with excess blasts (RAEB), and five had refractory anemia with excess blasts in transformation (RAEB-T); three patients could not be subclassified. The actuarial median survival for pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
1
6

Year Published

1987
1987
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(13 citation statements)
references
References 33 publications
0
6
1
6
Order By: Relevance
“…In myelofibrosis, the incidence of trisomy 8 was one in 15 cases of karyotype abnormalities in 47 patients (2%) at the time of diagnosis (15). The incidence of trisomy 8 was 54 of 713 cases (7.6%) in AML (16) and nine cases of 49 cases (18.4%) in MDS (17). The association of trisomy 8 in acute myeloid leukemia (AML), myelodysplastic syndrome (MDS) and chronic myeloproliferative disorder (CMPD) suggests that progression of the disease may have increased the incidence of trisomy 8 and development of leukemic transformation.…”
Section: Discussionmentioning
confidence: 99%
“…In myelofibrosis, the incidence of trisomy 8 was one in 15 cases of karyotype abnormalities in 47 patients (2%) at the time of diagnosis (15). The incidence of trisomy 8 was 54 of 713 cases (7.6%) in AML (16) and nine cases of 49 cases (18.4%) in MDS (17). The association of trisomy 8 in acute myeloid leukemia (AML), myelodysplastic syndrome (MDS) and chronic myeloproliferative disorder (CMPD) suggests that progression of the disease may have increased the incidence of trisomy 8 and development of leukemic transformation.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with HR MDS, median survival among larger study groups was reported to range between 8 and 18 months for RAEB and 4 and 15 months for RAEB‐t 3–5, 8. Although several more advanced prognostic models were subsequently developed based on multivariate analysis of variables,2–10 the FAB classification provided a basis for the first risk‐oriented management strategies.…”
mentioning
confidence: 99%
“…Die fünf Untergruppen des MDS nach der FAB-Klassifikation (2) lassen sich in zwei prognostisch unterschiedliche Krankheitsbilder aufteilen. Die FAB Subtypen mit geringem Blastenanteil im Knochenmark « 5 %) überleben im Median über 60 Monate (8,14) und gehen selten in eine akute Leukämie über (15 %) (übersicht bei 12), während die Subtypen mit höherem Blastenanteil (~5 %-30 %) im Median nur zwischen 5 und 25 Monate überleben und häufig eine Entwicklung zur akuten Leukämie aufweisen (bis 60 %) (12). Andere prognostische Faktoren wie Blastenanteil, Dysplasie von zwei oder drei Zellreihen oder Anteil der Mikromegakaryozyten sind nicht unabhängig von der oben genannten Einteilung nach der FAB-Klassifikation.…”
Section: Prognostische Faktorenunclassified
“…Andere prognostische Faktoren wie Blastenanteil, Dysplasie von zwei oder drei Zellreihen oder Anteil der Mikromegakaryozyten sind nicht unabhängig von der oben genannten Einteilung nach der FAB-Klassifikation. Nach Jakobs et al (14) trifft diese Aussage auch für die von Tricot et al (19) beschriebene Clusterbildung im Knochenmark zu, die zwar auf eine ungünstige Prognose hinweist, aber vorwiegend bei den Subtypen CMML, RAEB und RAEB-T vorkommt.…”
Section: Prognostische Faktorenunclassified